Efeito da adição de líquidos iônicos em um copolímero elastomérico para preparação de eletrólitos sólidos para baterias de íon lítio - Silva Filho, Sinval Braz da [UNIFESP] (2016)
The search for solid electrolytes for electrochemical devices (batteries, full cells) is object of intense research due to their benefits in comparison with the liquids, mainly due to the processability aspects, handling and leak elimination. Although studies involving solid polymeric electrolytes have 0been reported, the research for materials that combine good mechanical strength, elasticity, chemical and thermal stabilities and ionic conductivity is still emerging. In this context, the first part of this dissertation focuses on the preparation and characterization of solid polymeric electrolytes constituted by a commercial elastomer known as PEBAX-2533, containing 80% of polyether blocks (PE) and 20% of polyamide blocks (PA), modified with three different ionic liquids (EMImTf2N, EMImFAP, EMImTCB). In the next step, a lithium salt, LiTf2N, was added to PEBAX-2533 films containing 10% of the cited ionic liquids in order to produce solid polymer electrolytes for lithium ion batteries. PEBAX-2533 films containing more than 25% of the ionic liquids exhibited droplets on the surface of the film, indicating phase segregation. This was not observed for films containing 10% of the salt and therefore only these electrolytes were used in the further studies. The results showed that using this percentage, the ions of the ionic liquids are accommodated in the voids present in the amorphous regions of the elastomer. These films showed ionic conductivity around 10-6 Scm-1 at 25 ° C. When the lithium salt, LiTf2N, was added to these electrolytes of PEBAX-2533 and ionic liquids, the conductivity decreased due to the formation of aggregates of lithium cation and the anions of the ionic liquids, which have a low mobility, and therefore do not contribute for ionic conductivity. In addition, it was verified that the lithium clusters and ?free? Li+ also occupy the empty spaces on the elastomer and free Li+ establishes permanent ion-dipole interactions with the PE blocks. The electrolyte comprised of PEBAX-2533, ionic liquids and LiTf2N showed thermal stability up to 200 °C. With the addition of poly (ethylene oxide) (PEO) to PEBAX-2533 films containing 10% of EMImTf2N and LiTf2N at 40 °C, it was obtained an electrolyte with conductivity of 9.2 x 10-5 Scm-1.